Evaluation of dietary supplementation of omega-3 polyunsaturated fatty acids as an adjunct to scaling and root planing on salivary interleukin-1β levels in patients with chronic periodontitis: A clinico-immunological study - Vanali Vinodbhai Umrania; Pawar Chandrashekara Rao Deepika; Madhuri Kulkarni (Wolters Kluwer Medknow Publications, 2017)
Context: Host modulation with omega-3 polyunsaturated fatty acids (ω-3 PUFAs) has anti-inflammatory and pro-resolution actions through replacing and inhibiting metabolism of arachidonic acid (AA). Aim: This study was aimed at evaluating clinical parameters and salivary levels of interleukin-1 beta (IL-1β) after scaling and root planing (SRP) in chronic periodontitis patients, with and without dietary supplementation of ω-3 PUFAs. Settings and Design: Forty otherwise healthy participants with severe chronic periodontitis were included. Full-mouth periodontal examination and scaling and root planing were done for test and control group (20 participants each). Materials and Methods: The control group received SRP alone while test group received daily dose of 700 mg ω-3 PUFA capsules for 3 months. All clinical parameters were checked at baseline, 1 month, and 3 months' duration, whereas levels of IL-1β were checked in saliva at baseline and 3 months after therapy. Statistical Analysis Used: T-test and repeated measure analysis of variance were used with Statistical Package for the Social Science Windows software. Results: Improvements in all clinical outcomes were similar in both groups over 3 months. Improvements in clinical parameters were not statistically significant on intergroup comparison, except for improvement in Bleeding Index and reduction in levels of IL-1β, which were statistically significant in test group as compared to control group (P < 0.05). Conclusion: Even though adjunct therapy with ω-3 PUFAs can modulate cytokine levels and show proresolution properties, its importance on clinical outcomes may be controversial. Thus, this may be used as an adjunctive management of chronic periodontitis.